Research on the coopetition relationship and the development of city-industry integration of urban agglomeration under the effect of HSR - Tang, Zhaoping; Bi, Haosen; Sun, Jianping; Xu, Yun; Wang, Zhenyu (Frontiers in Environmental Science, 2023)
High-speed rail has influenced the evolution of coopetition relationships among regional cities and promoted city-industry integration development within urban agglomerations. Still, the specific impact it brings needs further study. This paper aims to assess how opening high-speed railways affect the economic development and pattern of urban agglomerations along the route under the perspective of industry-city integration, and the mechanism of action of urban agglomerations' coopetition relationships. The study is based on panel data from prefecture-level cities in Jiangxi Province, China, from 2014 to 2018. Through constructing an evaluation model of the degree of city-industry integration and an improved city economic linkage gravity model, we study the changes in the amount of economic linkage and affiliation of cities in Jiangxi Province after the opening of high-speed rail, which can analyze the changes in the structure and interconnectedness of each urban agglomeration. At the same time, an econometric model of the coopetition relationship of urban agglomerations is proposed to study the impact of high-speed rail on the economic cooperation of cities along the route in combination with the city-industry integration. The results show that 1) there are pronounced differences in the level of city-industry integration development of cities along the high-speed railway in Jiangxi Province, and the phenomenon is significantly improved by the improvement of inter-city economic links after the opening of the high-speed railway; 2) When cities enhance their fixed investment(FI) and labor force growth(LG), it has a significant promotion effect on their development, but will have a suppressing effect on other cities' city-industry integration, while when enhancing industrial concentration and human capital mobility, it can make the city-industry integration development of each city achieve a win-win situation; 3) The opening of high-speed rail enhances the economic ties of cities along the route and the radiation capacity of the original central cities, which is conducive to the formation of new central cities while improving the weak economic ties between urban agglomerations due to their geographical locations. This study proposes some conclusions and suggestions to provide research support for theories related to city-industry integration and policies related to urban agglomeration coopetition.